Paleoproduktivitas Formasi Tapak Banyumas Berdasarkan Bukti Mikrofosil - Dwijaya, Bayu Awifan; Prabowo, Romanus Edy; Waluyo, Gentur; Prayitno, Imam (Syntax Idea, 2021)
Tapak formation is a formation that is known to experience many changes in the ancient environment. This research was conducted in Tapak Formation, Mount Tugel, Banyumas Regency using bentonik and nannofosil foraminifera. Relative age analysis showed the sample age was around the initial pliocene, i.e. NN14 to no younger than NN15 (4.2 million years ago to lower than 3.5 million years ago). Paleoecological dynamics observed from abundance and diversity of microfossils experienced a decreased tendency from older samples to younger samples. Changes in paleoproductivity were observed based on primary and secondary productivity, where older samples tended to be higher than younger ones. Toc (Total Organic Carbon) content in older samples has a higher value than younger samples. The value of CaCO3 relatively increased in the younger direction, but in the A21N sample the percentage increased dramatically.